2016
DOI: 10.1920/re.ifs.2016.0115
|View full text |Cite
|
Sign up to set email alerts
|

Long-Run Trends in School Spending in England

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The reservation of such wealth to the already privileged is made worse by sequential cuts in state school funding, which fell by 9% per student in real terms between 2009-10 and 2019-20 -the biggest fall in over 40 years (Sibieta, 2020). A report by the Institute for Fiscal Studies (Sibieta 2021) showed that private schools now spend roughly 90% more per pupil than state school; a funding gap which had doubled between 2003-04 and 2020-21.…”
Section: Concluding Observationsmentioning
confidence: 99%
“…The reservation of such wealth to the already privileged is made worse by sequential cuts in state school funding, which fell by 9% per student in real terms between 2009-10 and 2019-20 -the biggest fall in over 40 years (Sibieta, 2020). A report by the Institute for Fiscal Studies (Sibieta 2021) showed that private schools now spend roughly 90% more per pupil than state school; a funding gap which had doubled between 2003-04 and 2020-21.…”
Section: Concluding Observationsmentioning
confidence: 99%
“…Given the cuts in public investment in education, for some LEAs to receive adequate funds based on pupil and school factors, others would have to face reduced investment in their schools. This created political tension, as the NFF was perceived as creating new 'winners ' and 'losers' among LEAs (BELFIELD;SIBIETA, 2016). It was not until the financial year 2018-19 that the NFF began to guide the allocation of education resources.…”
mentioning
confidence: 99%